Embracing heterogeneity: Why plural understandings strengthen interdisciplinarity and transdisciplinarity. (29th June 2022) - Vienni-Baptista, Bianca; Fletcher, Isabel; Lyall, Catherine; Pohl, Christian
Abstract: Interdisciplinarity and transdisciplinarity are seen as promising ways to address societies' grand challenges and so have become important topics in academic and policy discourses, particularly as part of discussions about mission-oriented knowledge production and research funding processes. However, there is an important disconnect between the way these terms are defined and used in the academic literature and the way they are defined and used in the policy literature. Academic writing on interdisciplinarity and transdisciplinarity offers plural understandings of both terms, whereas policy documents argue for concrete and simplified definitions. In this paper, we analyse the implications of these differences for research and funding. On the basis of an extensive literature review, we argue that the heterogeneity of understandings in interdisciplinarity and transdisciplinarity constitutes an asset. We advocate for the plurality of understandings to be used constructively in order to strengthen and promote effective research and research funding.